Pengaruh Penegakan Hukum Terhadap Perlindungan Hak Asasi Manusia Di Indonesia - M.Dede Al Farabi Suardi; Rachelya Putri Audrian; Lusya Najwa Vesca Hutagalung (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Human Rights (HAM) are fundamental rights inherent to every individual and must be respected and protected by the state. Law enforcement plays a crucial role in ensuring the protection of human rights in Indonesia, as regulated by various legal instruments such as Law No. 39 of 1999 and Law No. 26 of 2000. However, in practice, the enforcement of laws related to human rights violations still faces challenges, including weak integrity among law enforcement officers, impunity for perpetrators, and political interference that hinders fair and transparent judicial processes This study employs a normative juridical approach using secondary data sources to analyze the relationship between law enforcement and human rights protection in Indonesia. The findings indicate that effective law enforcement not only serves as a tool for prosecuting violations but must also include preventive measures through education, officer training, and the strengthening of legal norms that uphold human rights. Judicial reform, the empowerment of human rights enforcement institutions, and the utilization of digital technology are essential to enhance the effectiveness of law enforcement and expand access to justice and human rights information. Therefore, consistent, accountable law enforcement grounded in human rights principles can reinforce human rights protection in Indonesia, contributing to social justice and public welfare.